Rocuronium anaphylaxis in a 7-year-old boy during the induction of anesthesia. Issue 2 (3rd April 2018) - Morimoto, Yoshiko; Satake, Sakiko; Kamitani, Aguri; Yamada, Manabu; Saitou, Mutsumi; Torii, Yuki; Shiba, Rokuro; Hadase, Chika; Yamamoto, Toru
Abstract: We report a case of rocuronium-induced anaphylaxis in a previously healthy 7-year-old boy. The first presenting sign of anaphylaxis was bronchospasm, appearing 11 min after he received intravenous doses of rocuronium (1 mg/kg) (Eslax ®, MSD Co. Ltd., Tokyo, Japan), propofol (2 mg/kg), and cefazolin sodium (25 mg/kg). After the administration of adrenalin and ephedrine hydrochloride, bronchospasm resolved, and the vital signs became stable. Percutaneous pinning of his left humeral supracondylar fracture was performed without problems. The next day, he was successfully liberated from the ventilator support and discharged on the fifth hospital day. On the 76th postoperative day, we performed intradermal tests of rocuronium, propofol, and cefazolin. It showed that diluted rocuronium alone induced 14 mm of flare and 8 mm of wheal within 5 min, both of which disappeared within 15 min after the intradermal injection. The reaction was too quick to mention the possible contribution of rocuronium-specific IgE. His rapid reaction at the rocuronium skin test and anaphylactic reaction upon the first exposure to this drug may highlight the association of rocuronium anaphylaxis with IgE independent mast cell stimulation through mas-related G-protein coupled receptor X2 (MRGPRX2 receptor).